Characteristics of endophytic bacteria and active ingredients in the Eucommiae cortex from different origins - Liang, Xuejuan; Zhou, Kang; Li, Penghui; Wan, Dan; Liu, Jing; Yi, Xin; Peng, Yanmei (Frontiers in Microbiology, 2023)
Objective: This study aimed to explore the differences between Eucommia cortex (EC) endophytic bacteria from different origins and their effects on the active ingredients of EC. Methods: Ten samples of Eucommia ulmoides Oliv. (E. ulmoides) bark were collected from each of following four regions, namely, Zunyi in Guizhou (GZ), Baokang in Hubei (HUB), Cili in Hunan (HUN), and Loyang in Shaanxi (SX). Subsequently, the contents of the main active ingredients of EC were determined by ultra-performance liquid chromatography (UPLC), and the endophytic bacteria of EC were detected by 16S rRNA sequencing. The relationship between the dominant endophytic bacteria and the active ingredients was investigated by correlation analysis. Results: A total of 4551 different operational taxonomic units (OTUs) were delineated in the four groups of samples, of which 585, 439, 957, and 684 genera were annotated from GZ, HUB, HUN, and SX, respectively. The richness and diversity of endophytic bacteria from different origins were ranked as HUN > SX > GZ or HUB. The analysis demonstrated that there was no significant correlation between the diversity and richness of endophytic bacteria in EC and its active ingredients. Nevertheless, notable variations in the community structures of endophytic bacteria were observed across different origins, and they had a considerable impact on certain active ingredients in EC. Comamonas and Cedecea were the dominant genera. Characteristic bacteria of different origins could be clearly distinguished. Simultaneous, significant correlations had been identified between some characteristic endophytic bacteria derived from different origins and active ingredients of EC. For example, Delftia, a characteristic bacterium from GZ, showed a significant positive correlation with pinoresinol diglucoside. Paenibacillus and Klebsiella, two characteristic bacteria from HUB, exhibited significant positive correlations with geniposidic acid. Thauera, a characteristic bacterium from HUN, demonstrated a significant positive correlation with geniposide. Brevundimonas, a characteristic bacterium from SX, displayed a significant positive correlation with pinoresinol diglucoside. Conclusion: There was a complex correlation between EC endophytic bacteria and active ingredient content, while EC endophytic bacteria from different origins had significant differences at the genus level.